Daya Simpan Ikan Bandeng Yang Diawetkan Menggunakan Pengawet Alami Kombinasi Daun Salam (Eugenia polyantha, Weight.)Dan Garam - Sahputra, Nandhika W; , Triastuti Rahayu, S.Si, M.Si (2015)
Milk-Fish contains of 129 kkal of energy, 20 gram of protein, 150 gram of phosphore, 2 mg of iron, 20 gram of calsium, 4,8 gram of fat, 0,05 gram of vitamin-B1, 150 SI of vitamin-A dan 74 gram of water. It can make easily of damage for Milk-Fish body and suitable medium for bacterial growth. Natural preservatives which has antibacterial ability is combination of bay-leaves and salt. Bay leaves contains of tannin, flavonoid, and essential oil which serves as an antimicrobial, while a salt can be unravel into chloride ion and natrium ion which are toxic to microbes. The purpose of this study was determine the saving resources and the effect of the combination of bay leaves and salt on the milk-fish with the parameters of the number of bacteria, pH, water content and physical condition. The design of this study used a completely randomized design (CRD) with two factors, factor 1: concentration of bay leaf 0% (D0), 6% (D1), 7% (D2) and factors 2: the concentration of salt 0% (G0) , 7% (G1), and 8% (G2). The results show that fish has the best quality after 24 hours is treated D2G2 (bay leaves 7%, salt 8%) with the number of bacteria 6,10x10 /g of material, pH 6.7. The physical condition of the fish on D2G2 after 24 hours of treatment also better than other treatments. The surface is not covered by slime yet, has a fresh smell, no changes of color and fish rather soft texture, when it pressed former pressure fastly disappeared.